Semantic Content of Concept of TRUTH in Lexical-Semantic System of Russian Language (according to Lexicographic Sources) - E. E. Smirnova (Научный диалог)
The peculiarities of linguistic realization of the concept of TRUTH in the modern Russian language are revealed. The aim of the investigation is a complex cognitive-oriented analysis of the semantic content and cognitive characteristics of the concept of TRUTH according to the lexicographical sources. The research material are basic Russian etymological and explanatory dictionaries, phraseological dictionaries and paremiological sources. The study is based on theoretical principles of analysis of cultural-significant information. The study uses the methodology for the analysis of the concepts developed and tested in the works of scholars of Lobachevsky State University. The study identifies 7 cognitive signs of the concept of TRUTH: (1) what indicates real state of affairs; the truth; (2) the authenticity, truthfulness; (3) moral ideal, justice, goodness; (4) adequate reflection of objective reality in human consciousness (in philosophy); (5) the approval, judgment, established by science, proven by experience; (6) the idea of divine law; (7) banality. According to the author of the article, in the national conceptosphere there is the opposition of the concepts of PRAVDA and ISTINA ‘truth’ by the criterion of the evaluation ( pravda is estimated as more important than istina ). Practical significance of the research lies in the possibility to use its results in university teaching Russian as a foreign language, in compiling dictionaries of a new type - dictionaries of concepts and linguistic thesauri.